Applying Multiple Linear Regression Method to Measure the Impact of Human Capital, Social Media, Business Sector and Founder Gender on Advanced-Stage Startup Funding in Indonesia - Benedictus Hans; Eko Agus Prasetio (Research Synergy Foundation, 2023)
In recent years, there has been a significant increase in the growth of startups, particularly in developing nations. There are numerous opportunities for startups to innovate as a result of rapid technological growth, which can be used to improve the lives of many people across a variety of fields. Pioneering startups must place significant emphasis on investment, as it is a critical determinant of sustained business growth and innovation. A multitude of organizations are compelled to cease operations and innovation due to insufficient financial resources. Often, venture capital (VC) firms or angel investors provide financial support to startups. Each year, a venture capitalist may assess thousands of funding proposals from startups. It signifies that venture capital entry is competitive for each startup. The many factors that influence a venture capitalist's decision to invest in a startup have been the subject of numerous studies. This study employs a multiple linear regression model to examine the influence of human capital, social media, the business sector, and entrepreneur gender on funding for advanced-stage startups in Indonesia.